(3TQM GdMGhj GdUZjQs - (3Ydj Hf ESeGYjd Gdbhfhjs; (3GdbRhjfj , fLe GdOjf YHO GdZaGQ Hf YHO GdcjQe GdbRhjfj,J (B665 (3g` s
(3ChdgG (B:s
(3gPG eY GdELJgGO aj GdJhVjM bhdg HGH Cj gPG HGH CSbW GdJQGMe GdeTghQI s
(3BNQgG (B:s
(3hge Gdbhe Hfj WQhf Edi TF cPG bGdg GdLhgQi hGddg CYde HGdUhGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B267s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B625s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs